Preparation method of total heat exchange membrane
By vacuum-plating aluminum on the porous base film of the full heat exchange film and filling with hydrophilic composite filler, the problems of low thermal conductivity and insufficient functional performance of the existing full heat exchange film are solved, and higher thermal conductivity, moisture permeability and functional stability are achieved.
Patent Information
- Application Number
- CN202411663686.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing full heat exchange membrane has low thermal conductivity, and its mechanical properties, antibacterial, anti-mold and flame retardant properties are not good, which limits its application range.
The aluminum-plated layer is formed by vacuum plating on one side of the porous base film to improve the thermal conductivity and fill the other side with hydrophilic composite filler to enhance moisture permeability and functional performance.
It improves the thermal conductivity and moisture permeability of the full heat exchange membrane, enhances antibacterial, mildew and flame retardant properties, thereby improving the stability and durability of the membrane and expanding the application range.
Smart Images

Figure BDA0005144091680000091 
Figure BDA0005144091680000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of total heat exchange membranes, and in particular to a method for preparing a total heat exchange membrane. Background Art
[0002] As the core component of the total heat exchanger, the total heat exchange membrane plays a vital role in the fresh air system. Its core function is to exchange the temperature and humidity of indoor and outdoor air, realize energy recovery between outdoor fresh air and indoor polluted air, and thus improve energy efficiency and achieve energy conservation and emission reduction goals. However, the total heat exchange membranes currently circulating on the market generally have some shortcomings. Specifically, the thermal conductivity of the total heat exchange membrane is mostly in the range of 0.1-1.5W / m·K, which is relatively low. At the same time, its mechanical properties have not reached the ideal state, and its antibacterial, mildew-proof and flame-retardant properties are also poor, which to a certain extent limits its practical application.
[0003] The invention patent with publication number CN 103877870 B discloses a total heat exchange membrane and a total heat exchanger with antibacterial and anti-mildew functions, wherein the total heat exchange membrane comprises a functional layer, wherein the functional layer comprises a polymer and an antibacterial additive; and an optional support layer, wherein the functional layer is composited on the support layer. The total heat exchange membrane and the total heat exchanger of the invention can effectively prevent the growth of bacteria, mold and other organisms on the total heat exchange membrane during the long-term use process of providing fresh air indoors, removing dirty and harmful air, and recovering HVAC energy, but its thermal conductivity is still low, which cannot meet the requirements of efficient heat exchange, and it does not have good flame retardant properties, thereby limiting its long-term durability. Summary of the invention
[0004] In order to solve the above-mentioned technical problems, the present invention provides a method for preparing a full heat exchange membrane, which improves its thermal conductivity by aluminum plating on one side to meet the needs of efficient heat exchange, and at the same time fills the other side with a hydrophilic composite filler to ensure that it has good moisture permeability, as well as antibacterial, mildew-proof and flame-retardant properties, thereby improving the stability and durability of the full heat exchange membrane and expanding its application range.
[0005] The purpose of the present invention is achieved through the following technical solutions: The present invention provides a method for preparing a full heat exchange membrane, comprising the following steps: S1, vacuum-plating the porous base film with aluminum to form an aluminum-plated layer on one side of the porous base film; S2, forming a porous structure on one side of the aluminum coating layer by atomizing an acidic solution, wherein the obtained porous area accounts for 50-90% of the total area of the aluminum coating layer; S3. Coating the hydrophilic composite filler on the opposite side of the aluminum-plated layer on the porous base membrane to fill the pores of the porous base membrane and form a coating at the same time, and then drying to obtain a full heat exchange membrane.
[0006] The present invention forms a dense aluminum film by vacuum aluminum plating on the surface of the porous base film, which can greatly improve the thermal conductivity of the porous base film. However, if aluminum plating is performed on both sides of the porous base film, the flow rate during the indoor and outdoor air temperature and humidity exchange process will be greatly reduced. When the hydrophilic composite filler is subsequently coated, the water vapor permeation resistance will also be increased, and the adhesion of the hydrophilic composite filler will be affected. Even if the present invention is only aluminum-plated on one side of the surface of the porous base film, the water vapor permeation resistance will be increased, which will affect the total heat exchange efficiency. Therefore, it is necessary to control the area ratio of the porous formed after aluminum plating to ensure that the total heat exchange membrane has a higher thermal conductivity and water vapor permeation. In addition, the aluminum film is made porous by atomizing the acidic solution, and the chemical reaction of the metal aluminum and the acid solution is more active, and it is easy to control the area ratio of the porous formation. After the porous base film after aluminum plating is made into a total heat exchange membrane, aluminum will oxidize to form an aluminum oxide film, and aluminum oxide has good stability, thereby further improving the stability and durability of the total heat exchange membrane.
[0007] Preferably, the porous area of the obtained porous layer accounts for 60-80% of the total area of the aluminum coating layer.
[0008] Preferably, the thickness of the porous base membrane is 10-100 μm, more preferably 10-30 μm.
[0009] Preferably, the porous base film has a gram weight of 10-100 g / m 2 , more preferably 10-30g / m 2 .
[0010] Preferably, the material of the porous base membrane is one of polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polyamide (PA), thermoplastic polyurethane (TPU), polyimide (PI), polyphenylene sulfide (PPS), polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).
[0011] Preferably, the aluminum film has a thickness of 0.5-3 μm.
[0012] Preferably, the acidic solution is one of a hydrochloric acid solution and a sulfuric acid solution, and the hydrogen ion concentration is 6-9 mol / L.
[0013] Preferably, the atomized jet angle is 10-15°, the distance between the nozzle and the surface of the porous base membrane is 40-80 cm, the carrier gas is nitrogen, the nitrogen pressure is 2.5-4 bar, the feed rate is 30-50 L / min, the acidic solution pressure is 1.5-3 bar, and the feed rate is 5-7 L / h.
[0014] Preferably, the coating thickness of the hydrophilic composite filler is 1-200 μm, more preferably 10-40 μm.
[0015] Preferably, the hydrophilic composite filler comprises, by mass percentage, 1-5% of a hygroscopic agent, 1-5% of an antibacterial and mildewproof agent, 1-5% of a flame retardant and 1-5% of a hydrophilic polymer material, and the remainder is deionized water.
[0016] Preferably, the hydrophilic polymer material includes one or more of polyacrylic acid, polyvinyl alcohol, polyvinyl pyrrolidone and polydimethylacrylamide.
[0017] Preferably, the desiccant includes one or more of lithium chloride, calcium chloride, magnesium chloride and glycerol.
[0018] Preferably, the antibacterial and antifungal agent includes one or more of quaternary ammonium salt antibacterial agents, chlorophenol antibacterial agents, guanidine antibacterial agents, catechins, ginkgo extracts and matrine.
[0019] Preferably, the flame retardant includes one or more of phosphorus-nitrogen flame retardants.
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The aluminum coating can improve the thermal conductivity of the total heat exchange membrane, thereby improving the sensible heat exchange efficiency, and the aluminum coating can improve the mechanical properties; (2) By filling and coating the pores of the porous base film with a hydrophilic composite material, the water vapor permeability is increased and combined with the thermal conductivity of the aluminum coating layer, the total heat exchange efficiency can be further improved; (3) By filling and coating the pores of the porous base membrane with a hydrophilic composite filler, the added functional components can impart antibacterial, anti-mildew and flame retardant properties to the full heat exchange membrane. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0022] The preparation of the full heat exchange membrane includes the following steps: S1, vacuum-plating the porous base film with aluminum to form an aluminum-plated layer on one side of the porous base film; S2. A porous structure is formed on one side of the aluminum coating layer by atomizing an acidic solution, wherein the acidic solution is a hydrochloric acid solution or a sulfuric acid solution having a hydrogen ion concentration of 6-9 mol / L. After drying, the obtained porous area accounts for 50-90% of the total area of the aluminum coating layer; S3. Coat the hydrophilic composite filler on the opposite side of the aluminum-plated layer on the porous base membrane. The coating thickness of the hydrophilic composite filler is 1-200 μm, and the hydrophilic composite filler fills the pores of the porous base membrane. Then, dry it to obtain a full heat exchange membrane.
[0023] In a specific embodiment of the present invention, the thickness of the porous base film is 10-100 μm, and the weight is 10-100 g / m 2 The material of the porous base membrane is one of polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polyamide (PA), thermoplastic polyurethane (TPU), polyimide (PI), polyphenylene sulfide (PPS), polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).
[0024] In a specific embodiment of the present invention, vacuum aluminum plating is a conventional aluminum plating process, which is to form a dense aluminum film on the surface of the porous base film, and the thickness of the aluminum film is 0.5-3 μm.
[0025] In a specific embodiment of the present invention, the spray angle of the atomization is 10-15°, the distance between the nozzle and the surface of the porous base film is 40-80 cm, the carrier gas is nitrogen, the pressure of the nitrogen is 2.5-4 bar, the feed rate is 30-50 L / min, the pressure of the acidic solution is 1.5-3 bar, and the feed rate is 5-7 L / h. The porous base film is placed vertically in front of the atomization device, and the spray generated by the atomization device is used for spraying. The aluminum plating layer on the surface of the porous base film is atomized by the acidic solution. The spray amount per unit time is changed by adjusting the spray angle, nozzle distance and feed rate, and the atomization device is made to move linearly at a uniform speed through the slide rail to change the spraying position to form a porous structure. The calculation of the porous area ratio is: the weight of the porous base membrane is A (g), the weight of the porous base membrane after aluminum plating is X1 (g), the weight of the porous base membrane after atomization is X2 (g), and the porous area ratio (%) = (X2-X1) / (X1-A)*100%.
[0026] In a specific embodiment of the present invention, the hydrophilic composite filler includes 1-5% of a hygroscopic agent, 1-5% of an antibacterial and antifungal agent, 1-5% of a flame retardant and 1-5% of a hydrophilic polymer material, and the rest is deionized water, by mass percentage. In a specific embodiment of the present invention, the hydrophilic polymer material includes one or more of polyacrylic acid, polyvinyl alcohol, polyvinyl pyrrolidone and polydimethylacrylamide. The hygroscopic agent includes one or more of lithium chloride, calcium chloride, magnesium chloride and glycerol. The antibacterial and antifungal agent includes one or more of quaternary ammonium salt antibacterial agents, chlorophenol antibacterial agents, guanidine antibacterial agents, catechins, ginkgo extracts and matrine. The flame retardant includes one or more of phosphorus-nitrogen flame retardants (cyclic phosphates, tripolyphosphates, ammonium polyphosphate).
[0027] Example 1 The preparation of the full heat exchange membrane includes the following steps: S1, thickness 25μm, gram weight 15g / m 2 The porous PE base film is placed in a vacuum aluminum coating machine for vacuum aluminum coating, and an aluminum coating layer with a thickness of 1 μm is formed on one side of the PE base film.
[0028] S2. A porous structure is formed on one side of the aluminum-plated layer of the porous base membrane by atomizing an acidic solution. The acidic solution is a hydrochloric acid solution with a hydrogen ion concentration of 8 mol / L. The atomization is performed at the center of the aluminum-plated membrane. The atomization jet angle is 13°. The distance between the nozzle and the surface of the porous base membrane is 60 cm. The carrier gas is nitrogen. The pressure of the nitrogen is 3 bar and the feed rate is 48 L / min. The pressure of the acidic solution is 2 bar and the feed rate is 6.8 L / h. After drying, the obtained porous area accounts for 50.8% of the total area of the aluminum-plated layer.
[0029] S3, coating the hydrophilic composite filler on the opposite side of the aluminum layer on the porous base membrane, the hydrophilic composite filler includes 3% polyvinyl alcohol, 2% calcium chloride, 3% quaternary ammonium salt antibacterial agent (dodecyl trimethyl ammonium chloride) and 2% phosphorus nitrogen flame retardant (tripolyphosphate), and the rest is deionized water. The coating thickness of the hydrophilic composite filler is 20 μm, and the hydrophilic composite filler is filled in the porous, and dried to obtain a full heat exchange membrane.
[0030] Example 2 The preparation of the full heat exchange membrane includes the following steps: S1, thickness 25μm, gram weight 15g / m 2 The porous PE base film is placed in a vacuum aluminum coating machine for vacuum aluminum coating, and an aluminum coating layer with a thickness of 1 μm is formed on one side of the PE base film.
[0031] S2. A porous structure is formed on one side of the aluminum-plated layer of the porous base membrane by atomizing an acidic solution. The acidic solution is a hydrochloric acid solution with a hydrogen ion concentration of 8 mol / L. The atomization is performed at the center of the aluminum-plated membrane. The atomization jet angle is 13°. The distance between the nozzle and the surface of the porous base membrane is 60 cm. The carrier gas is nitrogen. The pressure of the nitrogen is 3 bar and the feed rate is 48 L / min. The pressure of the acidic solution is 2 bar and the feed rate is 6.8 L / h. After drying, the obtained porous area accounts for 62.3% of the total area of the aluminum-plated layer.
[0032] S3, coating the hydrophilic composite filler on the opposite side of the aluminum layer on the porous base membrane, the hydrophilic composite filler includes 3% polyvinyl alcohol, 2% calcium chloride, 3% quaternary ammonium salt antibacterial agent (dodecyl trimethyl ammonium chloride) and 2% phosphorus nitrogen flame retardant (tripolyphosphate), and the rest is deionized water. The coating thickness of the hydrophilic composite filler is 20 μm, and the hydrophilic composite filler is filled in the porous, and dried to obtain a full heat exchange membrane.
[0033] Example 3 The preparation of the full heat exchange membrane includes the following steps: S1, thickness 25μm, gram weight 15g / m 2 The porous PE base film is placed in a vacuum aluminum coating machine for vacuum aluminum coating, and an aluminum coating layer with a thickness of 1 μm is formed on one side of the PE base film.
[0034] S2. A porous structure is formed on one side of the aluminum-plated layer of the porous base membrane by atomizing an acidic solution. The acidic solution is a hydrochloric acid solution with a hydrogen ion concentration of 8 mol / L. The atomization is performed at the center of the aluminum-plated membrane. The atomization jet angle is 13°. The distance between the nozzle and the surface of the porous base membrane is 60 cm. The carrier gas is nitrogen. The pressure of the nitrogen is 3 bar and the feed rate is 48 L / min. The pressure of the acidic solution is 2 bar and the feed rate is 6.8 L / h. After drying, the obtained porous area accounts for 71.5% of the total area of the aluminum-plated layer.
[0035] S3, coating the hydrophilic composite filler on the opposite side of the aluminum layer on the porous base membrane, the hydrophilic composite filler includes 3% polyvinyl alcohol, 2% calcium chloride, 3% quaternary ammonium salt antibacterial agent (dodecyl trimethyl ammonium chloride) and 2% phosphorus nitrogen flame retardant (tripolyphosphate), and the rest is deionized water. The coating thickness of the hydrophilic composite filler is 20 μm, and the hydrophilic composite filler is filled in the porous, and dried to obtain a full heat exchange membrane.
[0036] Example 4 The preparation of the full heat exchange membrane includes the following steps: S1, thickness 25μm, gram weight 15g / m 2The porous PE base film is placed in a vacuum aluminum coating machine for vacuum aluminum coating, and an aluminum coating layer with a thickness of 1 μm is formed on one side of the PE base film; S2. A porous structure is formed on one side of the aluminum-plated layer of the porous base membrane by atomizing an acidic solution. The acidic solution is a hydrochloric acid solution with a hydrogen ion concentration of 8 mol / L. The atomization is performed at the center of the aluminum-plated membrane. The atomization jet angle is 13°. The distance between the nozzle and the surface of the porous base membrane is 60 cm. The carrier gas is nitrogen. The pressure of the nitrogen is 3 bar and the feed rate is 48 L / min. The pressure of the acidic solution is 2 bar and the feed rate is 6.8 L / h. After drying, the obtained porous area accounts for 80.1% of the total area of the aluminum-plated layer.
[0037] S3, coating the hydrophilic composite filler on the opposite side of the aluminum layer on the porous base membrane, the hydrophilic composite filler includes 3% polyvinyl alcohol, 2% calcium chloride, 3% quaternary ammonium salt antibacterial agent (dodecyl trimethyl ammonium chloride) and 2% phosphorus nitrogen flame retardant (tripolyphosphate), and the rest is deionized water. The coating thickness of the hydrophilic composite filler is 20 μm, and the hydrophilic composite filler is filled in the porous, and dried to obtain a full heat exchange membrane.
[0038] Example 5 The preparation of the full heat exchange membrane includes the following steps: S1, thickness 25μm, gram weight 15g / m 2 The porous PE base film is placed in a vacuum aluminum coating machine for vacuum aluminum coating, and an aluminum coating layer with a thickness of 1 μm is formed on one side of the PE base film.
[0039] S2. A porous structure is formed on one side of the aluminum-plated layer of the porous base membrane by atomizing an acidic solution. The acidic solution is a hydrochloric acid solution with a hydrogen ion concentration of 8 mol / L. The atomization is performed at the center of the aluminum-plated membrane. The atomization jet angle is 13°. The distance between the nozzle and the surface of the porous base membrane is 60 cm. The carrier gas is nitrogen. The pressure of the nitrogen is 3 bar and the feed rate is 48 L / min. The pressure of the acidic solution is 2 bar and the feed rate is 6.8 L / h. After drying, the obtained porous area accounts for 89.9% of the total area of the aluminum-plated layer.
[0040] S3, coating the hydrophilic composite filler on the opposite side of the aluminum layer on the porous base membrane, the hydrophilic composite filler includes 3% polyvinyl alcohol, 2% calcium chloride, 3% quaternary ammonium salt antibacterial agent (dodecyl trimethyl ammonium chloride) and 2% phosphorus nitrogen flame retardant (tripolyphosphate), and the rest is deionized water. The coating thickness of the hydrophilic composite filler is 20 μm, and the hydrophilic composite filler is filled in the porous, and dried to obtain a full heat exchange membrane.
[0041] Example 6 The difference from Example 3 is that the thickness of the aluminum plating layer is 1.5 μm.
[0042] The preparation of the full heat exchange membrane includes the following steps: S1, thickness 25μm, gram weight 15g / m 2 The porous PE base film is placed in a vacuum aluminum coating machine for vacuum aluminum coating, and an aluminum coating layer with a thickness of 1.5 μm is formed on one side of the PE base film.
[0043] S2. A porous structure is formed on one side of the aluminum-plated layer of the porous base membrane by atomizing an acidic solution. The acidic solution is a hydrochloric acid solution with a hydrogen ion concentration of 8 mol / L. The atomization is performed at the center of the aluminum-plated membrane. The atomization jet angle is 13°. The distance between the nozzle and the surface of the porous base membrane is 60 cm. The carrier gas is nitrogen. The pressure of the nitrogen is 3 bar and the feed rate is 48 L / min. The pressure of the acidic solution is 2 bar and the feed rate is 6.8 L / h. After drying, the obtained porous area accounts for 70.7% of the total area of the aluminum-plated layer.
[0044] S3, coating the hydrophilic composite filler on the opposite side of the aluminum layer on the porous base membrane, the hydrophilic composite filler includes 3% polyvinyl alcohol, 2% calcium chloride, 3% quaternary ammonium salt antibacterial agent (dodecyl trimethyl ammonium chloride) and 2% phosphorus nitrogen flame retardant (tripolyphosphate), and the rest is deionized water. The coating thickness of the hydrophilic composite filler is 20 μm, and the hydrophilic composite filler is filled in the porous, and dried to obtain a full heat exchange membrane.
[0045] Example 7 The difference from Example 3 is that the thickness of the aluminum plating layer is 2 μm.
[0046] The preparation of the full heat exchange membrane includes the following steps: S1, thickness 25μm, gram weight 15g / m 2 The porous PE base film is placed in a vacuum aluminum coating machine for vacuum aluminum coating, and an aluminum coating layer with a thickness of 2 μm is formed on one side of the PE base film.
[0047] S2. A porous structure is formed on one side of the aluminum-plated layer of the porous base membrane by atomizing an acidic solution. The acidic solution is a hydrochloric acid solution with a hydrogen ion concentration of 8 mol / L. The atomization is performed at the center of the aluminum-plated membrane. The atomization jet angle is 13°. The distance between the nozzle and the surface of the porous base membrane is 60 cm. The carrier gas is nitrogen. The pressure of the nitrogen is 3 bar and the feed rate is 48 L / min. The pressure of the acidic solution is 2 bar and the feed rate is 6.8 L / h. After drying, the obtained porous area accounts for 69.8% of the total area of the aluminum-plated layer.
[0048] S3, coating the hydrophilic composite filler on the opposite side of the aluminum layer on the porous base membrane, the hydrophilic composite filler includes 3% polyvinyl alcohol, 2% calcium chloride, 3% quaternary ammonium salt antibacterial agent (dodecyl trimethyl ammonium chloride) and 2% phosphorus nitrogen flame retardant (tripolyphosphate), and the rest is deionized water. The coating thickness of the hydrophilic composite filler is 20 μm, and the hydrophilic composite filler is filled in the porous, and dried to obtain a full heat exchange membrane.
[0049] Example 8 The difference from Example 3 is that the coating thickness of the hydrophilic composite filler is 10 μm.
[0050] The preparation of the full heat exchange membrane includes the following steps: S1, thickness 25μm, gram weight 15g / m 2 The porous PE base film is placed in a vacuum aluminum coating machine for vacuum aluminum coating, and an aluminum coating layer with a thickness of 1 μm is formed on one side of the PE base film.
[0051] S2. A porous structure is formed on one side of the aluminum-plated layer of the porous base membrane by atomizing an acidic solution. The acidic solution is a hydrochloric acid solution with a hydrogen ion concentration of 8 mol / L. The atomization is performed at the center of the aluminum-plated membrane. The atomization jet angle is 13°. The distance between the nozzle and the surface of the porous base membrane is 60 cm. The carrier gas is nitrogen. The pressure of the nitrogen is 3 bar and the feed rate is 48 L / min. The pressure of the acidic solution is 2 bar and the feed rate is 6.8 L / h. After drying, the obtained porous area accounts for 71.7% of the total area of the aluminum-plated layer.
[0052] S3, coating the hydrophilic composite filler on the opposite side of the aluminum layer on the porous base membrane, the hydrophilic composite filler includes 3% polyvinyl alcohol, 2% calcium chloride, 3% quaternary ammonium salt antibacterial agent (dodecyl trimethyl ammonium chloride) and 2% phosphorus nitrogen flame retardant (tripolyphosphate), and the rest is deionized water. The coating thickness of the hydrophilic composite filler is 10 μm, and the hydrophilic composite filler is filled in the porous, and dried to obtain a full heat exchange membrane.
[0053] Example 9 The difference from Example 3 is that the coating thickness of the hydrophilic composite filler is 40 μm.
[0054] The preparation of the full heat exchange membrane includes the following steps: S1, thickness 25μm, gram weight 15g / m 2 The porous PE base film is placed in a vacuum aluminum coating machine for vacuum aluminum coating, and an aluminum coating layer with a thickness of 1 μm is formed on one side of the PE base film.
[0055] S2. A porous structure is formed on one side of the aluminum-plated layer of the porous base membrane by atomizing an acidic solution. The acidic solution is a hydrochloric acid solution with a hydrogen ion concentration of 8 mol / L. The atomization is performed at the center of the aluminum-plated membrane. The atomization jet angle is 13°. The distance between the nozzle and the surface of the porous base membrane is 60 cm. The carrier gas is nitrogen. The pressure of the nitrogen is 3 bar and the feed rate is 48 L / min. The pressure of the acidic solution is 2 bar and the feed rate is 6.8 L / h. After drying, the obtained porous area accounts for 71.4% of the total area of the aluminum-plated layer.
[0056] S3, coating the hydrophilic composite filler on the opposite side of the aluminum layer on the porous base membrane, the hydrophilic composite filler includes 3% polyvinyl alcohol, 2% calcium chloride, 3% quaternary ammonium salt antibacterial agent (dodecyl trimethyl ammonium chloride) and 2% phosphorus nitrogen flame retardant (tripolyphosphate), and the rest is deionized water. The coating thickness of the hydrophilic composite filler is 40 μm, and the hydrophilic composite filler is filled in the porous, and dried to obtain a full heat exchange membrane.
[0057] Example 10 The difference from Example 3 lies in the composition and coating thickness of the hydrophilic composite filler.
[0058] The preparation of the full heat exchange membrane includes the following steps: S1, thickness 25μm, gram weight 15g / m 2 The porous PE base film is placed in a vacuum aluminum coating machine for vacuum aluminum coating, and an aluminum coating layer with a thickness of 1 μm is formed on one side of the PE base film.
[0059] S2. A porous structure is formed on one side of the aluminum-plated layer of the porous base membrane by atomizing an acidic solution. The acidic solution is a hydrochloric acid solution with a hydrogen ion concentration of 8 mol / L. The atomization is performed at the center of the aluminum-plated membrane. The atomization jet angle is 13°. The distance between the nozzle and the surface of the porous base membrane is 60 cm. The carrier gas is nitrogen. The pressure of the nitrogen is 3 bar and the feed rate is 48 L / min. The pressure of the acidic solution is 2 bar and the feed rate is 6.8 L / h. After drying, the obtained porous area accounts for 72.0% of the total area of the aluminum-plated layer.
[0060] S3, coating the hydrophilic composite filler on the opposite side of the aluminum layer on the porous base membrane, the hydrophilic composite filler includes 4% polyvinyl alcohol, 3% calcium chloride, 3% quaternary ammonium salt antibacterial agent (dodecyl trimethyl ammonium chloride) and 3% phosphorus nitrogen flame retardant (tripolyphosphate) by mass percentage, and the rest is deionized water. The coating thickness of the hydrophilic composite filler is 40 μm, and the hydrophilic composite filler is filled in the porous, and dried to obtain a full heat exchange membrane.
[0061] Embodiment 11 The difference from Example 3 is that the thickness of the porous base film is 30 μm and the weight is 20 g / m 2 .
[0062] The preparation of the full heat exchange membrane includes the following steps: S1, thickness 30μm, weight 20g / m 2 The porous PE base film is placed in a vacuum aluminum coating machine for vacuum aluminum coating, and an aluminum coating layer with a thickness of 1 μm is formed on one side of the PE base film.
[0063] S2. A porous structure is formed on one side of the aluminum-plated layer of the porous base membrane by atomizing an acidic solution. The acidic solution is a hydrochloric acid solution with a hydrogen ion concentration of 8 mol / L. The atomization is performed at the center of the aluminum-plated membrane. The atomization jet angle is 13°. The distance between the nozzle and the surface of the porous base membrane is 60 cm. The carrier gas is nitrogen. The pressure of the nitrogen is 3 bar and the feed rate is 48 L / min. The pressure of the acidic solution is 2 bar and the feed rate is 6.8 L / h. After drying, the obtained porous area accounts for 71.8% of the total area of the aluminum-plated layer.
[0064] S3, coating the hydrophilic composite filler on the opposite side of the aluminum layer on the porous base membrane, the hydrophilic composite filler includes 3% polyvinyl alcohol, 2% calcium chloride, 3% quaternary ammonium salt antibacterial agent (dodecyl trimethyl ammonium chloride) and 2% phosphorus nitrogen flame retardant (tripolyphosphate), and the rest is deionized water. The coating thickness of the hydrophilic composite filler is 20 μm, and the hydrophilic composite filler is filled in the porous, and dried to obtain a full heat exchange membrane.
[0065] Comparative Example 1 The difference from Example 3 is that aluminum plating is not performed.
[0066] The preparation of the full heat exchange membrane includes the following steps: The hydrophilic composite filler is coated on a surface with a thickness of 25 μm and a gram weight of 25 g / m 2 On one side of the porous PE base film, the hydrophilic composite filler includes 3% polyvinyl alcohol, 2% calcium chloride, 3% quaternary ammonium salt antibacterial agent (dodecyl trimethyl ammonium chloride) and 2% phosphorus nitrogen flame retardant (tripolyphosphate), and the rest is deionized water. The coating thickness of the hydrophilic composite filler is 20μm, and the hydrophilic composite filler is filled in the porous, and dried to obtain a full heat exchange membrane.
[0067] Comparative Example 2 The difference from Example 3 is that the thickness of the aluminum plating is 5 μm.
[0068] The preparation of the full heat exchange membrane includes the following steps: S1, thickness 25μm, gram weight 15g / m 2The porous PE base film is placed in a vacuum aluminum coating machine for vacuum aluminum coating, and an aluminum coating layer with a thickness of 5 μm is formed on one side of the PE base film.
[0069] S2. A porous structure is formed on one side of the aluminum-plated layer of the porous base membrane by atomizing an acidic solution. The acidic solution is a hydrochloric acid solution with a hydrogen ion concentration of 8 mol / L. The atomization is performed at the center of the aluminum-plated membrane. The atomization jet angle is 13°. The distance between the nozzle and the surface of the porous base membrane is 60 cm. The carrier gas is nitrogen. The pressure of the nitrogen is 3 bar and the feed rate is 48 L / min. The pressure of the acidic solution is 2 bar and the feed rate is 6.8 L / h. After drying, the obtained porous area accounts for 71.3% of the total area of the aluminum-plated layer.
[0070] S3, coating the hydrophilic composite filler on the opposite side of the aluminum layer on the porous base membrane, the hydrophilic composite filler includes 3% polyvinyl alcohol, 2% calcium chloride, 3% quaternary ammonium salt antibacterial agent (dodecyl trimethyl ammonium chloride) and 2% phosphorus nitrogen flame retardant (tripolyphosphate), and the rest is deionized water. The coating thickness of the hydrophilic composite filler is 20 μm, and the hydrophilic composite filler is filled in the porous, and dried to obtain a full heat exchange membrane.
[0071] Comparative Example 3 The difference from Example 3 is that the thickness of the hydrophilic composite filler coating is 100 μm.
[0072] The preparation of the full heat exchange membrane includes the following steps: S1, thickness 25μm, gram weight 15g / m 2 The porous PE base film is placed in a vacuum aluminum coating machine for vacuum aluminum coating, and an aluminum coating layer with a thickness of 1 μm is formed on one side of the PE base film.
[0073] S2. A porous structure is formed on one side of the aluminum-plated layer of the porous base membrane by atomizing an acidic solution. The acidic solution is a hydrochloric acid solution with a hydrogen ion concentration of 8 mol / L. The atomization is performed at the center of the aluminum-plated membrane. The atomization jet angle is 13°. The distance between the nozzle and the surface of the porous base membrane is 60 cm. The carrier gas is nitrogen. The pressure of the nitrogen is 3 bar and the feed rate is 48 L / min. The pressure of the acidic solution is 2 bar and the feed rate is 6.8 L / h. After drying, the obtained porous area accounts for 71.5% of the total area of the aluminum-plated layer.
[0074] S3, coating the hydrophilic composite filler on the opposite side of the aluminum layer on the porous base membrane, the hydrophilic composite filler includes 3% polyvinyl alcohol, 2% calcium chloride, 3% quaternary ammonium salt antibacterial agent (dodecyl trimethyl ammonium chloride) and 2% phosphorus nitrogen flame retardant (tripolyphosphate), and the rest is deionized water. The coating thickness of the hydrophilic composite filler is 100 μm, and the hydrophilic composite filler is filled in the porous, and dried to obtain a full heat exchange membrane.
[0075] Test standard: Water vapor transmission rate: GB / T 1037-2021, 38°C, 90%RH; Thermal conductivity: ISO 22007-2-2008; Tensile strength: GB / T 1040.2-2022.
[0076] Table 1 As shown in Table 1, the present invention improves the thermal conductivity of the total heat exchange membrane through the aluminum coating layer, and increases the water vapor permeability by filling and coating the pores of the porous base membrane with a hydrophilic composite filler, thereby further improving the total heat exchange efficiency, and the aluminum coating layer can improve the mechanical properties. Examples 1-5 show that when the porous area accounts for a gradually larger proportion of the total area of the aluminum coating layer, the water vapor permeability of the total heat exchange membrane increases, and the thermal conductivity also decreases, but it is still significantly higher than the thermal conductivity of the conventional total heat exchange membrane (not aluminum-plated) in the prior art. Combined with Comparative Example 1, it also shows that although aluminum plating of the porous base membrane in the present invention will reduce the water vapor permeability, the subsequent acid solution atomization and hydrophilic composite filler coating can balance the water vapor permeability and thermal conductivity, so that the comprehensive performance of the total heat exchange membrane is higher. Example 3 and Example 6-7 show that the greater the thickness of the aluminum coating, the smaller the fluctuation of the thermal conductivity coefficient due to the constant porous area formed by controlling the atomization, but it will affect the water vapor permeability to a certain extent. Comparative Example 2 also shows that too large a thickness of the aluminum coating will lead to too low a water vapor permeability, and the improvement of the thermal conductivity coefficient is not significant, and it will lead to excessively high costs. Example 3 and Examples 8-10 show that the coating thickness of the hydrophilic composite filler will affect the water vapor permeability, and the excessive thickness in Comparative Example 3 will also have a greater impact on the thermal conductivity. Example 3 and Example 11 show that increasing the thickness of the porous base film will reduce the water vapor permeability, and increasing the thickness will affect the thermal conductivity.
[0077] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a total heat exchange membrane, characterized in that: The steps include: S1, vacuum-plating the porous base film with aluminum to form an aluminum-plated layer on one side of the porous base film; S2, forming a porous structure on one side of the aluminum coating by atomizing an acidic solution, wherein the obtained porous area accounts for 50-90% of the total area of the aluminum coating; S3. Coating the hydrophilic composite filler on the opposite side of the aluminum-plated layer on the porous base membrane to fill the pores of the porous base membrane and form a coating at the same time, and then drying to obtain a full heat exchange membrane.
2. The method for preparing the total heat exchange membrane according to claim 1, characterized in that: The thickness of the porous base film is 10-100 μm.
3. The method for preparing the total heat exchange membrane according to claim 1, characterized in that: The acidic solution is one of a hydrochloric acid solution and a sulfuric acid solution.
4. The method for preparing a total heat exchange membrane according to any one of claims 1 to 3, characterized in that: The atomized jet angle is 10-15°, the distance between the nozzle and the surface of the porous base membrane is 40-80 cm, the carrier gas is nitrogen, the pressure of the nitrogen is 2.5-4 bar, and the pressure of the acid solution is 1.5-3 bar.
5. The method for preparing a total heat exchange membrane according to any one of claims 1 to 3, characterized in that: The coating thickness of the hydrophilic composite filler is 1-200 μm.
6. The method for preparing the total heat exchange membrane according to claim 1, characterized in that: Calculated by mass percentage, the hydrophilic composite filler includes 1-5% of a hygroscopic agent, 1-5% of an antibacterial and mildew-proof agent, 1-5% of a flame retardant and 1-5% of a hydrophilic polymer material, and the rest is deionized water.
7. The method for preparing the total heat exchange membrane according to claim 6, characterized in that: The hydrophilic polymer material includes one or more of polyacrylic acid, polyvinyl alcohol, polyvinyl pyrrolidone and polydimethylacrylamide.
8. The method for preparing the total heat exchange membrane according to claim 6, characterized in that: The desiccant includes one or more of lithium chloride, calcium chloride, magnesium chloride and glycerol.
9. The method for preparing a total heat exchange membrane according to any one of claims 6 to 8, characterized in that: The antibacterial and antifungal agent comprises one or more of quaternary ammonium salt antibacterial agents, chlorophenol antibacterial agents, guanidine antibacterial agents, catechins, ginkgo extracts and matrine.
10. The method for preparing a total heat exchange membrane according to any one of claims 6 to 8, characterized in that: The flame retardant includes one or more phosphorus-nitrogen flame retardants.
Citation Information
Patent Citations
Total heat exchange membrane and total heat exchanger with antibacterial and anti-mildew functions
CN103877870B
Heat-conducting aluminum-based copper-clad plate and preparation method thereof
CN116476467A
High-moisture-permeability composite total heat exchange membrane and preparation method thereof
CN117924798A
Flexible conductive barrier film and preparation method and application thereof
CN118418556A
Heat exchange membrane, its preparing process and heat exchanger with it
CN1603105A